Norms of some operators from bergman spaces to weighted and Bloch-type spaces - Stević, Stevo (Utilitas Mathematica, 2008)
We calculate the norm of weighted composition operators uCψ from the Bergman space Aα p (B) to the weighted space H μ ∞(B) on the unit ball B, and norms of products of Volterra and composition operators between the weighted Bergman space and the Bloch-type space on the unit disk.